Pengaruh Disposisi Matematis Mahasiswa pada Pembelajaran Hybrid Learning Terhadap Prestasi Belajar Mahasiswa - Fajar Lestari (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
This study aims to determined the effect of students' mathematical dispositions when applying the hybrid learning model to student achievement in the mathematics education undergraduate program at Wahidiyah University in the even semester of the 2021/2022 academic year. This research was a quantitative research with survey method. The sampling technique in this study used saturated sampling. The data collection method used is the documentation of the final semester exam results for student achievement data and a questionnaire for students' mathematical disposition data. In this study using a simple regression test which is calculated using the SPSS v.26 for Windows program. The research data were tested for normality, linearity, and simple regression. The regression model equation Y = 0.760 + 0.983 X + means that every 1% increase in mathematical disposition will result in an increase in mathematics learning achievement of 0.98 and vice versa. The conclusion of this study was that the mathematical disposition of students when learning Hybrid Learning affects student learning achievement positively and significantly where the influence of students' mathematical dispositions on learning Hybrid Learning on student learning achievement is 96.6% and the remaining 3.4% is influenced by other variables not examined in this research.